Exchange bias at low fields exhibited by the interface between epitaxial layers of ferromagnetic and charge‐ordered rare‐earth manganites. Issue 8 (28th June 2016) - Saha, Rana; Vasu, K.; Negi, D. S.; Datta, R.; Sundaresan, A.; Rao, C. N. R.
Abstract : Epitaxial thin films of ferromagnetic La0.7 Sr0.3 MnO3 (LSMO) and charge‐ordered, antiferromagnetic Y0.5 Ca0.5 MnO3 (YCMO) were deposited on SrTiO3 (100) substrates by pulsed laser deposition (PLD). The heterostructure undergoes tetragonal distortion due to strong biaxial tensile strain imposed by the substrate. The LSMO–YCMO bilayers exhibit significant exchange bias (EB) across the interface even in a very small remnant magnetic field (∼5 Oe) present in the superconductor magnet. The unidirectional exchange anisotropy at the interface can be switched by reversing the polarity of the remnant magnetic field. Significant asymmetry in the M ( H ) loop is exhibited by the heterostructure interface under cooling in the presence of small remnant magnetic field ( H r ∼ 5 Oe). (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : This study presents to the occurrence of significant exchange bias in magnetic thin‐film heterostructures even in the presence of a very small remnant magnetic field (∼5 Oe). This phenomenon has been demonstrated in the interface between the epitaxial layers of charge‐ordered antiferromagnetic Y0.5 Ca0.5 MnO3 and ferromagnetic La0.7 Sr0.3 MnO3 .